Pengaruh Stres Kerja Terhadap Kinerja Karyawan Studi Kasus Pada Kampung Batik Laweyan Surakarta) - Yulianto, Dedy; , Lukman Hakim, S.E., M.Si (2015)
The purpose of this study is to analyze the effect of work stress on employee performance Batik Mahkota company, Batik Merak Manis, Batik Putra Laweyan Surakarta.Populasi this study are Company employees Batik Mahkota, Batik Merak Manis, Batik Putra Laweyan Surakarta. Based on the partial test results showed that the variables of environmental stress does not affect the performance of the employee, partial test results showed that the stress variables organization does not affect the performance of the employee, partial test results showed that the stress variables affect the performance of individual employees. F-test analysis results unknown environmental stress variables (X1), stressed the organization (X2) and individual stress (X3) have significant influence jointly on employee performance. Based on the calculation results obtained regression determination coefficient R = 0.233 can be said that 22.3 environmental stress variables (X1), stressed the organization (X2) and individual stress (X3) influence on the performance of employees, while the remaining 77.7% is due to the influence of other variables which is not covered in this study. Keywords: Job Stress and Employee Performance